Trees immune to cutting in Park Halfeld, Juiz de Fora/MG: a case study on policies and preservation values - Cunha, Caio Freitas; Unanue, Mariane Garcia; Colchete Filho, Antonio Ferreira (Paisagem e Ambiente, 2020)
This article aims to address the case of two trees in the city of Juiz de Fora that were declared immune to cutting as a sample of public policies for the preservation of urban vegetation, aiming to reveal their contribution to urban life, including symbolic and affective aspects of their relationship with the inhabitants. The case study is adopted as a methodological axis, with a qualitative bias, using the bibliographic research of studies dedicated to the concept ofaffective landscape, the Forest Code (2012) and the municipal decrees that grant immunity to cut to certain trees in the locality. Combining this effort with data collection through photographic and satellite images, it was possible to verify the conservation status of trees immune to cutting, their planting conditions, care and integration with the surroundings, observing the degree of success of public policies for protection of native and exotic species found here. It is concluded that the efforts to evaluate potential trees that are candidates for cutting immunity in Juiz de Fora take little into account the affective and symbolic elements of the relationship between the trees and the population, which results in the selection of specimens with little social and historical interactionwith the surrounding population and the city.